Original paperUterine perforation and its dosimetric implications in cervical cancer high-dose-rate brachytherapy - Bahadur, Yasir A.; Eltaher, Maha M.; Hassouna, Ashraf H.; A. Attar, Mohammad; Constantinescu, Camelia (Journal of Contemporary Brachytherapy, 2015)
Purpose : To retrospectively assess the incidence of sub-serosal and uterine perforation of intra-uterine tandem in intracavitary high-dose-rate (HDR) brachytherapy for cervical cancer, and to evaluate its dosimetric implications on computed tomography (CT)-based treatment planning. Material and methods : Computed tomography images and brachytherapy plans of cervical cancer patients treated from February 2006 to December 2012 were reviewed for sub-optimal implants (sub-serosal and uterine perforation), and their correlation with cancer FIGO stage and patients’ age. For each patient, the plans showing sub-optimal insertion of intra-uterine tandem were analyzed and compared to plans with adequate insertion. The difference in dose coverage of clinical-target-volume (CTV) and variation of the dose delivered to organs-at-risk (OARs) rectum and bladder were evaluated. Results : A total of 231 brachytherapy plans for 82 patients were reviewed. We identified 12 (14.6%) patients and 14 (6%) applications with uterine perforation, and 12 (14.6%) patients and 20 (8.6%) applications with sub-serosal insertion of tandem. Data analysis showed that advanced stage correlates with higher incidence of sub-optimal implants (p = 0.005) but not the age (p = 0.18). Dose-volume-histograms (DVHs) analysis showed large variations for CTV dose coverage: D90 significantly decreased with average of –115.7% ± 134.9% for uterine perforation and –65.2% ± 82.8% for sub-serosal insertion (p = 0.025). The rectum and bladder dose assessed by D2cc increased up to 70.3% and 43.8%, respectively, when sub-optimal insertion of uterine tandem occurred. Conclusions : We report a low incidence of uterine perforation and sub-serosal insertion of uterine tandem in intracavitary HDR brachytherapy for cervical cancer. However, the effects on treatment plan dosimetry can be considerably detrimental. Therefore, we recommend image-guided insertion, at least for the challenging cases.